Levels of identity in lower middle class highschool students - García Ampudia, Lupe (2000)
One worked with school of room and recruit of secondary, coming from low middle class of four educational centers belonging to the cone this and north to analyze the characteristics of identity in their levels: national, generational, regional, of gender, relative and personnel. For the gathering of the data an instrument was elaborated based on the inventory of identity of Zavalloni that establishes the relationship between the subjective science and the attributes social objectives, the answers of the fellows they were coded with its respective frequencies and classified in function of its positive orientation, negative or neuter, finally the positive answers and negatives were classified in five categories: instrumental, affective, social, moral and polítical. The results indicated the predominant presence of the instrumental answers and the positive orientation of the answers in each one of the levels, being more evident those referred to the identity generational and family.